Research on Task Priority Model and Algorithm for Satellite Scheduling Problem - Jian Wu; Jiawei Zhang; Jinghui Yang; Lining Xing (IEEE Access, 2019)
In satellite scheduling system, one of the most important issues is task scheduling. Most of the existing algorithms focused on the scenario of normal tasks with fixed priority and don’t consider emergency tasks. However, emergency tasks in satellite scheduling system have the independent arrival time and execution deadline. To deal with this challenge, we propose the task scheduling model, task priority model, and task scheduling algorithms based on rolling-horizon optimization (RHO) strategy to manage the tasks. In task scheduling model, we construct a scheduling model with multiple constraint conditions. In task priority model, we decompose task priority into four parts, including target priority, imaging task priority, TT&C (track, telemetry, control) requirement priority, and data transmission requirement priority, and describe the factors corresponding to each priority based on the actual engineering. The RHO strategy is designed with a periodical triggering mode, and scheduling process is decomposed into a series of static scheduling intervals, the dynamic scheduling of emergency tasks is realized by optimizing the scheduling schemes in each interval. Meanwhile, task scheduling algorithms, including heuristic algorithm, genetic algorithm, and NSGA-II algorithm, are designed to solve the proposed task scheduling model. Our simulation results show that the proposed task priority model and RHO strategy are effective, which can significantly improve the number of overall tasks and emergency tasks. Meanwhile, each task scheduling algorithm has different performances in the processing time and optimal objectives.